2016
DOI: 10.1136/archdischild-2016-310475
|View full text |Cite
|
Sign up to set email alerts
|

Early puberty in 11-year-old girls: Millennium Cohort Study findings

Abstract: ObjectiveEarly puberty in girls is linked to some adverse outcomes in adolescence and mid-life. We address two research questions: (1) Are socioeconomic circumstances and ethnicity associated with early onset puberty? (2) Are adiposity and/or psychosocial stress associated with observed associations?DesignLongitudinal data on 5839 girls from the UK Millennium Cohort Study were used to estimate associations between ethnicity, family income, adiposity and psychosocial stress with a marker of puberty.Main outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
52
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 44 publications
(46 reference statements)
3
52
1
3
Order By: Relevance
“…Thirteen longitudinal studies , conducted mostly in developed countries, evaluated the associations between birth weight and menarcheal age, reporting risk estimates from regression analysis (Table ). Menarcheal age was significantly associated with birth weight in 10 of the 13 studies , while three studies did not find an association. A Filipino study found no association between age at menarche and absolute birth weight; however, girls born lighter and longer than the sample median weight (3 kg) and length (49 cm), respectively, had the highest hazard of menarche at any given age during the study period (from birth to 15 years; HR = 1.54; p < 0.01, compared to girls born >3 kg and <49 cm) .…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen longitudinal studies , conducted mostly in developed countries, evaluated the associations between birth weight and menarcheal age, reporting risk estimates from regression analysis (Table ). Menarcheal age was significantly associated with birth weight in 10 of the 13 studies , while three studies did not find an association. A Filipino study found no association between age at menarche and absolute birth weight; however, girls born lighter and longer than the sample median weight (3 kg) and length (49 cm), respectively, had the highest hazard of menarche at any given age during the study period (from birth to 15 years; HR = 1.54; p < 0.01, compared to girls born >3 kg and <49 cm) .…”
Section: Resultsmentioning
confidence: 99%
“…In combination, the candidate factors explored by Kelly et al 2 explained only a minority of the social and ethnic group patterning in menarche timing in the Millennium Cohort Study (table 1). So what other explanations might there be?…”
mentioning
confidence: 99%
“…The paper by Kelly et al 2 describes substantial patterning by socioeconomic and ethnic background in the prevalence of early age at menarche (the first menstrual period, a late milestone of puberty in girls). They analysed freely available data from the Millennium Cohort Study, a very large prospective UK birth cohort, enriched for socially disadvantaged groups.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Female adolescent facing menarche at a young age will face differences in their later stage in life compared to teenagers experiencing normal puberty period because this is in related to the increasing risk of pre-marital sex and teen pregnancy, low mental in teenagers, heart disease, and other malignant diseases such as ovarian cancer, breast cancer (Kelly et al, 2016).…”
Section: Introductionmentioning
confidence: 99%